Dithienylbenzodiimide: a new electron-deficient unit for n-type polymer semiconductors. Issue 37 (4th August 2017) - Chen, Jianhua; Zhang, Xianhe; Wang, Gang; Uddin, Mohammad Afsar; Tang, Yumin; Wang, Yulun; Liao, Qiaogan; Facchetti, Antonio; Marks, Tobin J.; Guo, Xugang
Abstract : A novel imide-functionalized dithienylbenzodiimide was synthesized and incorporated into polymer semiconductors, which exhibit low-lying FMOs and substantial electron mobilities. Abstract : Inspired by the excellent device performance of imide-functionalized polymer semiconductors in organic electronics, a novel imide-based building block, dithienylbenzodiimide (TBDI), with fused backbone is designed and synthesized. Single-crystal structure analysis reveals that the TBDI unit features non-planar backbone conformation but with a tight π-stacking distance of 3.36 Å. By copolymerizing with various electron-rich co-units, a series of TBDI-based polymer semiconductors is synthesized and the optoelectronic, thermal, electrochemical and charge transport properties of the semiconductors are characterized. Attributed to the non-planar backbone and intrinsic electrical property of TBDI, all polymers exhibit wide bandgaps (∼2.0 eV) with low-lying HOMOs (<−5.5 eV). Organic thin-film transistors are fabricated by incorporating the TBDI-based polymers as the active layer to investigate their charge transport properties. The dithienylbenzodiimide-bithiophene copolymer shows ambipolar transport characteristics with an electron and hole mobility of 0.15 and 0.015 cm 2 V −1 s −1, respectively. By incorporating weaker electron donor co-units, the dithienylbenzodiimide–thiophene and dithienylbenzodiimide–difluorobithiophene copolymers exhibit unipolar n-channel transistor performance with electron mobility up to 0.11 and 0.34 cm 2 V −1 s −1, respectively. Most high-performance n-channel polymer semiconductors reported to date typically show narrow bandgaps with high-lying HOMOs, resulting in substantial p-channel performance. The new TBDI-based wide bandgap polymers with low-lying HOMOs greatly suppress p-channel performance and lead to improved I on / I off ratios. The excellent n-channel performance is attributed to the strong electron-withdrawing capability of imide groups, low-lying frontier molecular orbitals, compact π-stacking distance, and a high degree of film crystallinity as confirmed by GIWAXS analysis with distinct interlamellar and π-stacking diffraction patterns. The result reveals that a building block with non-planar backbone can be utilized for constructing high crystalline polymer semiconductors with substantial charge carrier mobility. The study indicates that dithienylbenzodiimide is a promising unit for synthesizing wide bandgap polymeric semiconductors with unipolar n-channel performance.